In situ synchrotron powder diffraction study of the setting reaction kinetics of magnesium-potassium phosphate cements. (January 2016) - Viani, Alberto; Peréz-Estébanez, Marta; Pollastri, Simone; Gualtieri, Alessandro Francesco
Abstract: This work reports a kinetic study of the formation of magnesium-potassium phosphate cements accomplished using in-situ synchrotron powder diffraction. The reaction: MgO + KH2 PO4  + 5H2 O → MgKPO4  · 6H2 O was followed in situ in the attempt of contributing to explain the overall mechanism and assess the influence of periclase (MgO) grain size and calcination temperature (1400-1600 °C) on the reaction kinetics. Numerical kinetic parameters for the setting reaction have been provided for the first time. The best fit to the kinetic data was obtained using a weighted nonlinear model fitting method with two kinetic equations, representing two consecutive, partially overlapping processes. MgO decomposition could be described by a first order (F1) model followed by a Jander diffusion (D3) controlled model. Crystallization of the product of reaction was modelled using an Avrami model (An ) followed by a first order (F1) chemical reaction. A reaction mechanism accounting for such results has been proposed.